2015
DOI: 10.3168/jds.2015-9529
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of skin condition by oral supplementation with sphingomyelin-containing milk phospholipids in a double-blind, placebo-controlled, randomized trial

Abstract: Sphingomyelin (SM), an essential phospholipid for the skin, is contained largely in the milk fat globule membrane surrounding milk fat, concentrated fractions of which are also generated concurrently during the manufacture of dairy products. Such an SM-containing milk phospholipid concentrate (SM-MPC) is useful for investigating the benefits of dietary SM. Here, we examined the effect of consuming SM-MPC on the condition of skin in a double-blind, placebo-controlled, randomized trial. Ninety-six healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Morifuji and co-workers [ 111 ] fed female hairless mice with low and high concentration of milk phospholipids, and they reported that mice on a diet with supplemented with a high phospholipid concentration showed higher covalently-bound ω-hydroxy ceramides in the epidermis and, generally, an improved skin barrier function due to the suppression of skin inflammation. Higurashi et al [ 112 ] carried out their experimentation on human subjects orally supplemented by a commercial SM-containing milk phospholipid concentrate containing 5.9% of SM; their results showed that subjects supplemented with phospholipids reported higher skin elasticity below the eye than control subjects. The authors attributed this beneficial effect to an enhanced synthesis of ceramides from SM that led to the production of extracellular matrix and, because of that, improved skin elasticity.…”
Section: Health Benefits Provided By Colostrum Milk and Dairy By-mentioning
confidence: 99%
“…Morifuji and co-workers [ 111 ] fed female hairless mice with low and high concentration of milk phospholipids, and they reported that mice on a diet with supplemented with a high phospholipid concentration showed higher covalently-bound ω-hydroxy ceramides in the epidermis and, generally, an improved skin barrier function due to the suppression of skin inflammation. Higurashi et al [ 112 ] carried out their experimentation on human subjects orally supplemented by a commercial SM-containing milk phospholipid concentrate containing 5.9% of SM; their results showed that subjects supplemented with phospholipids reported higher skin elasticity below the eye than control subjects. The authors attributed this beneficial effect to an enhanced synthesis of ceramides from SM that led to the production of extracellular matrix and, because of that, improved skin elasticity.…”
Section: Health Benefits Provided By Colostrum Milk and Dairy By-mentioning
confidence: 99%
“…Further, these molecules contribute to the proper development of immunity and intestinal trophism, possibly mediated by the evolving microbiota. The second area where MFGM is being positioned is the prevention of several diseases including cardiovascular disease [12], impaired bone turnover and inflammation [13], skin conditions [14], and infection by E. coli [15], as well as age-associated diseases such as cognitive decline and muscle loss. Stemming from the observation that the phospholipid composition of MFGM is quite similar to that of neuronal cell membranes, some investigators are proposing the use of MFGM to counteract the loss of some neuronal components such as polyunsaturated fatty acids (PUFAs), namely those of the omega-3 series [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Milk‐derived products used in modern cosmetic industry usually include cow milk or whey. Anti‐inflammatory and skin rejuvenating effects of mare milk have been documented on skin fibroblasts, the dermal cells responsible for collagen synthesis and secretion 27,28 . A beneficial effect of ingested milk and related dairy products on skin physiology and acne treatment has been highlighted in some publications 29‐31 .…”
Section: Discussionmentioning
confidence: 99%